2022
DOI: 10.3390/biom12020264
|View full text |Cite
|
Sign up to set email alerts
|

Human β-Defensin 2 (HBD-2) Displays Oncolytic Activity but Does Not Affect Tumour Cell Migration

Abstract: Defensins form an integral part of the cationic host defence peptide (HDP) family, a key component of innate immunity. Apart from their antimicrobial and immunomodulatory activities, many HDPs exert multifaceted effects on tumour cells, notably direct oncolysis and/or inhibition of tumour cell migration. Therefore, HDPs have been explored as promising anticancer therapeutics. Human β-defensin 2 (HBD-2) represents a prominent member of human HDPs, being well-characterised for its potent pathogen-killing, wound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Although the underlying interaction mechanism between oncolytic peptides and plasma membrane is not fully elucidated, several techniques have been employed to characterize the mode of action of oncolytic peptides towards tumor cells, such as X-ray diffraction, surface plasmon resonance, attenuated total reflectance-fourier transform infrared (ATR-FTIR) spectroscopy, confocal fluorescence microscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), circular dichroism (CD) spectroscopy, flow cytometry and molecular dynamics simulation (MD simulation), etc. [ [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. In general, the oncolytic peptides-mediated cancer cell killing can be roughly divided into four main stages: (1) oncolytic peptides are attracted to the cancer cell surface via electrostatic interaction between the negatively charged cytoplasmic membrane components and the positively charged peptides residues [ 65 ]; (2) additional hydrophobic interactions between the phospholipid hydrophobic tail and the residues of the non-polar peptide serve to facilitate the embedding of oncolytic peptides into tumor cells membranes via multiple theoretical models [ 38 ]; (3) the membrane curvature would be changed, subsequently, the structure and integrity of the cells membrane were disrupted (e.g., blebbing, pore formation, and vascularization) [ 71 ]; (4) tumor cells are lysed and the intracellular contents would be released [ 68 ].…”
Section: Function Mechanism and Structure-activity Relationship Of On...mentioning
confidence: 99%
“…Although the underlying interaction mechanism between oncolytic peptides and plasma membrane is not fully elucidated, several techniques have been employed to characterize the mode of action of oncolytic peptides towards tumor cells, such as X-ray diffraction, surface plasmon resonance, attenuated total reflectance-fourier transform infrared (ATR-FTIR) spectroscopy, confocal fluorescence microscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), circular dichroism (CD) spectroscopy, flow cytometry and molecular dynamics simulation (MD simulation), etc. [ [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. In general, the oncolytic peptides-mediated cancer cell killing can be roughly divided into four main stages: (1) oncolytic peptides are attracted to the cancer cell surface via electrostatic interaction between the negatively charged cytoplasmic membrane components and the positively charged peptides residues [ 65 ]; (2) additional hydrophobic interactions between the phospholipid hydrophobic tail and the residues of the non-polar peptide serve to facilitate the embedding of oncolytic peptides into tumor cells membranes via multiple theoretical models [ 38 ]; (3) the membrane curvature would be changed, subsequently, the structure and integrity of the cells membrane were disrupted (e.g., blebbing, pore formation, and vascularization) [ 71 ]; (4) tumor cells are lysed and the intracellular contents would be released [ 68 ].…”
Section: Function Mechanism and Structure-activity Relationship Of On...mentioning
confidence: 99%
“…Furthermore, hBD-2 and -3 were reported to contain an oncolytic motif that binds to phosphatidylinositol 4,5-bisphosphate. This interaction is critical for mediating cytolysis of tumor cells, and experiments with hBD-2 showed that the defensin killed tumor cells via acute lytic cell death instead of apoptosis [ 46 , 47 ]. Other research confirmed this, as A549 adenocarcinoma cells treated with hBD-3 displayed immediate cell membrane damage.…”
Section: Direct Effect On Tumor Cellsmentioning
confidence: 99%
“…While chemical synthesis has been used to produce most of the abovementioned molecules, the production cost for defensins is still too high, and synthetic defensins analogues are needed (Bindra et al, 2022 ). Some modifications were carried out in the N‐terminal amphipathic domain and in C‐terminal hydrophobic groups of cecropins.…”
Section: Molecular Structure‐based Classification Of Antibacterialsmentioning
confidence: 99%